2004
DOI: 10.1523/jneurosci.2235-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Tlx, an Orphan Nuclear Receptor, Regulates Cell Numbers and Astrocyte Development in the Developing Retina

Abstract: Tlx belongs to a class of orphan nuclear receptors that underlies many aspects of neural development in the CNS. However, the fundamental roles played by Tlx in the control of eye developmental programs remain elusive. By using Tlx knock-out (KO) mice, we show here that Tlx is expressed by retinal progenitor cells in the neuroblastic layer during the period of retinal layer formation, and it is critical for controlling the generation of appropriate numbers of retinal progenies through the activities of cell cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
111
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(120 citation statements)
references
References 48 publications
7
111
1
1
Order By: Relevance
“…Tll is also expressed in undifferentiated proliferating neural precursor cells at the third instar larval stage, the last larval stage before eclosion into adult flies, indicating that tll may have an essential function in neuronal stem cells [11]. Consistent with the findings in Drosophila, mouse Tlx is expressed in the developing central nervous system (CNS) from embryonic day 8 (E8) until E13.5 and in retinal progenitor cells (RPCs) from E11.5 until E17.5 during retinal development [5,[30][31][32]. At the embryonic stage, Tlx expression presents a graded pattern in the telencephalon along the dorsalventral axis with a high level in the dorsal-lateral region and a low level in the ventral-medial region [33].…”
Section: Tlx Expression Its Targets and Related Signal Pathwaysmentioning
confidence: 63%
See 3 more Smart Citations
“…Tll is also expressed in undifferentiated proliferating neural precursor cells at the third instar larval stage, the last larval stage before eclosion into adult flies, indicating that tll may have an essential function in neuronal stem cells [11]. Consistent with the findings in Drosophila, mouse Tlx is expressed in the developing central nervous system (CNS) from embryonic day 8 (E8) until E13.5 and in retinal progenitor cells (RPCs) from E11.5 until E17.5 during retinal development [5,[30][31][32]. At the embryonic stage, Tlx expression presents a graded pattern in the telencephalon along the dorsalventral axis with a high level in the dorsal-lateral region and a low level in the ventral-medial region [33].…”
Section: Tlx Expression Its Targets and Related Signal Pathwaysmentioning
confidence: 63%
“…It controls the generation of proper numbers of RPCs by activating cyclin-D1 and p27 during early retinal layer formation [31]. Further, Tlx expression has been found in Müller glial cells and mature astrocytes of the inner nuclear layer after birth and temporarily in immature astrocytes before migration from the optic nerve to the inner nuclear layer [31]. Consistently, reduced retinal size and cell number, optic nerve degeneration, and visual impairment have been reported in Tlxdeficient mice [32,45,65].…”
Section: Roles Of Tlx Homologues In Regulation Of Retinal Progenitor mentioning
confidence: 85%
See 2 more Smart Citations
“…This interpretation is in keeping with the fact that N-cadherin is expressed in vascular endothelia (Luo and Radice, 2005;Navarro et al, 1998). The situation is less clear for M- (Tomi et al, 2004) and R-cadherin (Dorrell et al, 2002); the latter, however has been reported to be expressed in (retinal) astroglia (Miyawaki et al, 2004). This said, it follows from straightforward numerical considerations that most Math1-GFP negative cells expressing M-, N-and R-cadherin are indeed (postmitotic) granule cells.…”
Section: Comparison Of Our Cadherin Data With Previous Results -Qualimentioning
confidence: 84%